2020
DOI: 10.2355/tetsutohagane.tetsu-2019-118
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy in Hydrogen Embrittlement Resistance of Drawn Pearlitic Steel Investigated by <i>in-situ</i> Microbending Test during Cathodic Hydrogen Charging

Abstract: To investigate causes of superior hydrogen embrittlement resistance of drawn pearlitic steel, notched microcantilevers with different notch orientations were fabricated by focused ion beam, and microbending tests were conducted in air and during cathodic hydrogen charging by electrochemical nanoindentation. In air, indentation load increased with increase in indentation displacement, and no crack appeared for any notch orientations. During hydrogen charging, indentation load declined, and a crack appeared. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Focusing on the subcrack tip, crack-tip blunting was observed perpendicular to the cementite lamella. Tomatsu et al reported that the ferrite/cementite interface was the preferential crack propagation path due to hydrogen embrittlement in drawn pearlitic steel (carbon content: 0.94 %C) 21) . Regarding the S45C pearlite in this study, the crackpropagation path was along the lamellar interface of the pearlite, and the cementite located in a direction different from the crack-propagation direction might have hindered crack propagation.…”
Section: Fractography and Hydrogen Embrittlement Mechanism Of Linear ...mentioning
confidence: 99%
“…Focusing on the subcrack tip, crack-tip blunting was observed perpendicular to the cementite lamella. Tomatsu et al reported that the ferrite/cementite interface was the preferential crack propagation path due to hydrogen embrittlement in drawn pearlitic steel (carbon content: 0.94 %C) 21) . Regarding the S45C pearlite in this study, the crackpropagation path was along the lamellar interface of the pearlite, and the cementite located in a direction different from the crack-propagation direction might have hindered crack propagation.…”
Section: Fractography and Hydrogen Embrittlement Mechanism Of Linear ...mentioning
confidence: 99%